2016
DOI: 10.1016/j.cmpb.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

ECG-based heartbeat classification for arrhythmia detection: A survey

Abstract: An electrocardiogram (ECG) measures the electric activity of the heart and has been widely used for detecting heart diseases due to its simplicity and non-invasive nature. By analyzing the electrical signal of each heartbeat, i.e., the combination of action impulse waveforms produced by different specialized cardiac tissues found in the heart, it is possible to detect some of its abnormalities. In the last decades, several works were developed to produce automatic ECG-based heartbeat classification methods. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
340
0
23

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 713 publications
(403 citation statements)
references
References 140 publications
1
340
0
23
Order By: Relevance
“…After preprocessing, segmentation divides the signal into smaller segments, which can better express the electrical activity of the heart [1]. Nowadays, the researchers can get good results from preprocessing and segmentation by some popular techniques or tools [2]. Therefore, most of the literature focuses upon the last two phases.…”
Section: Introductionmentioning
confidence: 99%
“…After preprocessing, segmentation divides the signal into smaller segments, which can better express the electrical activity of the heart [1]. Nowadays, the researchers can get good results from preprocessing and segmentation by some popular techniques or tools [2]. Therefore, most of the literature focuses upon the last two phases.…”
Section: Introductionmentioning
confidence: 99%
“…It is disturb and able to made a misinterpretation of ECG signal analysis. We used cubic spline filtering as developed by Badilini [19]. The study used cubic spline interpolation to reduce the baseline noise signal, because this interpolation can remove the wondering of isoelectric with no significant influent to the ECG signal.…”
Section: Signal Preprocessingmentioning
confidence: 99%
“…The important features were: Age, Gender, the ECG signal amplitude for each sample (millivolts), RR interval (inter-beat interval in milliseconds), WABP (arterial blood pressure in millivolts) and instantaneous heart rate measured at the 'instance' when the abnormal heart beat annotation occurred in ECG recording. These feature vectors were derived for 4 annotation types: V (Premature Ventricular Contraction: PVC), A (Atrial Premature Beat: APB), L (Left bundle branch block beat), R (Right bundle branch block beat) [6] [7] [29]. It has been observed that these 4 annotation types do occur in ECG recordings of healthy subjects as well and can go unnoticed without showing any symptoms [30].…”
Section: A Ecg Waveform Dataset Preparation and Analysismentioning
confidence: 99%